Взаємодія норм трудового права і правового регулювання - Якушев, І.; Iakushev, I. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Стаття присвячена класифікації норм трудового права з врахуванням особливостей методу вказаної галузі права. Розглянуто взаємозалежність виду норм права і методу правового регулювання у трудовому праві. Розкрито значення норми права у застосуванні методів і способів правового регулювання трудових та тісно пов’язаних з ними відносин. The article is devoted to the classification of labor law norms in accordance with the peculiarities of this branch of law methodology. The author considers the interdependence of law norms types and methods of legal regulation in labor law. He assumes that rules of law operate as a form/method of their legal regulation and, alternatively, the methods of legal regulation determine the content of the law norms. To determine the methods and ways of legal regulation in the law it is advisable to classify the mandatory rules into absolutely explicit and relatively definite, depending on the nature of prescriptions. The dispositive rules can be classified into the dispositive - mandatory and the dispositive-optional ones. This classification would allow the subjects of lawmaking to regulate social relations, using one or the other type of the regulations or their optimal ratio for the sake of the effectiveness of legal regulations. The emphasis is laid on the importance of norms of law in the application of appropriate method and way of legal regulation of labor and other closely related to them relations.
Interaction of Labor Law Norms and Legal Regulations
Keywords: норма трудового права; класифікація норм трудового права; метод трудового права; norm of labor law; the classification of labor law; labor law method